1999
DOI: 10.1016/s0035-9203(99)90045-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of formalin fixation on the polymerase chain reaction characterization of Entamoeba histolytica

Abstract: Formalin fixation is the most common storage, transportation and preservation method for stool samples. However, fixation dramatically reduces our ability to extract from stool samples DNA that is a suitable template for polymerase chain reaction (PCR)-based diagnostic tests. In this study we evaluated the effects of formalin concentration and of the time stored in fixative on the success of PCR amplification. We found that the deleterious effects of formalin are both time and concentration dependent and may r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…PVA and SAF preserve trophozoites and cysts, and formalin preserves cysts for examination in wet mounts. However, methods of fixation of feces with fixatives or preservatives may result in a decreased sensitivity of PCR with time (143,192). A few groups have, however, shown good results using formalin-fixed samples for PCR (147,157).…”
Section: Complexity Of Fecal Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…PVA and SAF preserve trophozoites and cysts, and formalin preserves cysts for examination in wet mounts. However, methods of fixation of feces with fixatives or preservatives may result in a decreased sensitivity of PCR with time (143,192). A few groups have, however, shown good results using formalin-fixed samples for PCR (147,157).…”
Section: Complexity Of Fecal Samplesmentioning
confidence: 99%
“…Ethanol is a simple transport medium that preserves amebic DNA. The most widely used reagent for the preservation of fecal samples is 10% buffered formalin solution (120); however, this solution is reported to hamper product amplification by PCR because of the interfering nature of the fixative, which perfuses the organisms and reacts with DNA (143). Consequently, freezing a fresh fecal specimen at Ϫ20°C before extraction of DNA is a better strategy, as it does not affect the sensitivity of the molecular assays (52,105,123).…”
Section: Complexity Of Fecal Samplesmentioning
confidence: 99%
“…Microscopic examination of intestinal parasites is usually performed on fixed stools. Numerous groups have tried with variable success molecular methods on this type of sample, and recently, the effect of formalin fixation on PCR was further investigated (17). It was shown that even if its effect on DNA is indirect, concentrations of formalin higher than 1% seemed to inhibit PCR amplification from 4 days of fixation.…”
mentioning
confidence: 99%
“…The negative influence of formalin on various stages of intestinal parasites was reported by, e.g. Ramos et al (1999), who showed that preservation of stool samples in 10% buffered formalin for more than 7 days hampered successful PCR amplification of DNA of the trophozoite Entamoeba histolytica . Contrastingly, Paglia and Visca (2004) demonstrated results of a study in which nested PCR, with initial amplification of the 1076-bp fragment of the SSU rRNA gene, had been applied for the specific detection of E. histolytica/Entamoeba dispar in faeces fixed in 10% formalin for 90 days.…”
Section: Discussionmentioning
confidence: 85%